2019
DOI: 10.1080/13102818.2019.1604158
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of MGMT promoter methylation in diffuse glioma patients

Abstract: Current treatment options for diffuse glioma patients include maximum safe resection followed by a combination of radiation therapy and chemotherapy with alkylating agents. The DNA-repair enzyme O 6 -methylguanine-DNA methyltransferase (MGMT) counteracts the cytotoxic effect of alkylating agents and mediates chemoresistance. Disruption of the DNA methylation mechanism in diffuse glioma cells results in epigenetic silencing of MGMT through methylation of cytidinephosphate-guanosine dinucleotides (CpG) in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This was much longer than older patients (>80 years), who had a survival time of 1.6 months [ 32 ]. Furthermore, Jovanović et al observed that in comparison to younger patients, people over the age of 50 had considerably poorer overall survival rates (median survival ranged from 7 to 19 months) [ 24 ], which is in accordance with our results. The OS in our younger study group was over twice as long (20 months with methylation and 14 months without methylation) as in the older group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was much longer than older patients (>80 years), who had a survival time of 1.6 months [ 32 ]. Furthermore, Jovanović et al observed that in comparison to younger patients, people over the age of 50 had considerably poorer overall survival rates (median survival ranged from 7 to 19 months) [ 24 ], which is in accordance with our results. The OS in our younger study group was over twice as long (20 months with methylation and 14 months without methylation) as in the older group.…”
Section: Discussionsupporting
confidence: 92%
“…Even in patients with nonresectable GBM, promoter methylation status played a crucial role in the survival prognosis [ 29 ]. Conversely, Jovanovic et al showed that MGMT promoter methylation was not associated with the survival results of diffuse glioma patients [ 24 ]. In our study, 18 out of 41 patients had MGMT promoter methylation, which accounted for 43%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSP data were analyzed using the previously reported semi-quantitative approach, which relies on an ImageJ software comparison of the intensities of the methylated (M) and unmethylated (U) MSP bands ( Figure S6 in the Supplementary Materials ) [ 23 ]. In this manner, the MGMT methylation status was evaluated in 36 glioma patients and 3 negative control samples (meningioma, hemangiopericytoma, and peripheral blood leukocytes of a healthy individual).…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to make a new effort to resolve the dilemma of whether the MGMT promoter methylation status has prognostic value for diffuse glioma samples from Serbian patients. Previously, although a significant improvement was observed in overall survival with TMZ treatment (the median survival was 15 months) in comparison with diffuse glioma patients without treatment (the median survival was 5 months), it was not interrelated with the MGMT promoter methylation status [ 22 , 23 ]. Currently, the MGMT promoter methylation status is investigated in the context of the clinical data, the choice of method for its assessment (real-time methylation-specific PCR (qMSP) vs. previous methylation-specific PCR (MSP)), and the IDH1 /2 mutation status.…”
Section: Introductionmentioning
confidence: 99%